Analisis Kemampuan Literasi Matematika Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa - Erika Setiowati; Syamsul Hadi; Maria Ulfa; Ahmad Dainuri; Fajar Sholeh; Miftahus Surur; Zainul Munawwir (CV. Aksara Global, 2024)
Mathematical literacy is a person's ability to formulate, use and interpret mathematics in various contexts of daily life problems efficiently. Literacy skills students not only have numeracy skills but also the ability to think logically and critically in solving problems. Mathematical literacy has a significant positive impact on students' critical thinking abilities. This research aims to describe the influence of mathematical literacy on students' critical thinking abilities in mathematics subjects. The method used in this research is a literature review. The results of this research show a strong relationship between mathematical literacy and critical thinking skills. Mathematical literacy involves understanding, using, and interpreting mathematical concepts in a variety of concepts, while critical thinking skills involve analysis, evaluation, and rational decision making. Mastery of mathematical literacy can improve students' critical thinking abilities, because mathematics involves problem solving and logical reasoning. Thus, developing mathematical literacy can contribute to improving students' critical thinking abilities